2004
DOI: 10.1007/bf02708207
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast chemistry in complex and confined systems

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 97 publications
1
9
0
Order By: Relevance
“…Law [ 15 ] reported that solvent diffusional rotation causes shorter measured lifetimes. Multiexponential relaxation dynamics that were dominated by solvent relaxation constants were also found by Dutta and Bhattacharyya [ 79 ], who reported lifetime constants in the low picosecond range and in the low nanosecond range, whereby the nanosecond range carried significant information about the type of solvent. Hara et al .…”
Section: Engineering Aspects Of Molecular Viscometerssupporting
confidence: 65%
“…Law [ 15 ] reported that solvent diffusional rotation causes shorter measured lifetimes. Multiexponential relaxation dynamics that were dominated by solvent relaxation constants were also found by Dutta and Bhattacharyya [ 79 ], who reported lifetime constants in the low picosecond range and in the low nanosecond range, whereby the nanosecond range carried significant information about the type of solvent. Hara et al .…”
Section: Engineering Aspects Of Molecular Viscometerssupporting
confidence: 65%
“…Moving beyond the proximal solvent shells, force field calculations predict that solvent shell structure varies continuously, as a function of distance. Experimentally mapping out the molecular dynamics over this coordinate is challenging. The archetypal systems to investigate solvent–surface interactions are confined volumes, such as reverse micelles, porous silica, and zeolites . 2D-IR studies of water in reverse micelles have shown conclusively that spectral diffusion varies continuously with the volume of the solvent pool and is not well described as a core of bulk-like solvent independent of a shell of surface-like solvent. ,,, However, these measurements invariably probe a vibrational mode on the solvent molecules, which captures spectral diffusion from molecules in all possible environments within the pore rather than providing the information as a function of distance from the wall.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, there have been many studies of time-dependent fluorescence (TDF). [4][5][6][7][8][9][10][11][12] In these experiments, a dye molecule with an electronic charge-transfer transition is excited and the resulting fluorescence is monitored as a function of time. The changes in fluorescence energy with time provide information about the reorganization of the solvent around the dye molecule in response to a change in its dipole moment upon excitation.…”
Section: Introductionmentioning
confidence: 99%